Дослiдження дисперсiї швидкостi пружних хвиль в опромiнених кристалах LiF - Petchenko, G. O.; Petchenko, O. M. (Publishing house "Academperiodika", 2018)
The influence of a preliminary deformation (the residual strain e = 0.65%) and x-ray irradiation to exposure doses of 0–800 R on the frequency dependence of the sound velocity, v(f), in LiF crystals in the frequency interval from 7.5 to 232.5 MHz and at room temperature has been studied using the pulsed technique. By extrapolating the results obtained for v(f) to the low-frequency interval and using the well-known theoretical relations, the coefficient of dynamic viscosity B and the dislocation density Λ were found to be independent of the irradiation dose. At the same time, the absolute values of B were found to be lower and the values of Λ higher by an order of magnitude than the corresponding values obtained with the use of the most reliable techniques, such as the methods of high-frequency internal friction and etch pit counting, respectively.